If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(3x + 7) = 0 Reorder the terms: -4(7 + 3x) = 0 (7 * -4 + 3x * -4) = 0 (-28 + -12x) = 0 Solving -28 + -12x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '28' to each side of the equation. -28 + 28 + -12x = 0 + 28 Combine like terms: -28 + 28 = 0 0 + -12x = 0 + 28 -12x = 0 + 28 Combine like terms: 0 + 28 = 28 -12x = 28 Divide each side by '-12'. x = -2.333333333 Simplifying x = -2.333333333
| 3(9-2)-3cubed= | | 1x-2=1.5 | | 81=8z-7 | | [5x]+5=45 | | 4x-1+4x+1=56 | | -6x-4=-2(3x+2) | | -5(2)+y=-10 | | 4(x-1)+8=24 | | (K+38.5)+42.3=2k+(51*1+10.5) | | 3x=x+22 | | -5(0)+y=-10 | | 18+4(x)=0 | | 18+4(x)=50 | | 3.60-(1.60+0.05x)=0 | | -5(0)+y=-20 | | (3x-7)(4x-5)+x=5 | | -3(4-2x)=12-6x | | [-6m]=30 | | -3+2t=13 | | Y-x=11 | | 72-x=4x+32 | | 1x+2=1.5 | | 3y-5=7y-13 | | -100+4(x)=0 | | -1=9y-25 | | 4=2t-12 | | -100+4(x)=(-50) | | Z+-22=-96 | | -5(-2)+y=-10 | | 9.6t-8.6t+2.6=9.7 | | 5y-7+1y=(1y+3y) | | 2+5(-5y-3)=-2(7y-3)+3 |